Oligomeric phenylpropanoids having new skeletons and hypoglycemic activity from Magnolia officinalis var. biloba. Issue 17 (1st July 2021) - Xu, Kailing; Li, Chuan; Li, Chuangjun; Ma, Jie; Zang, Yingda; Ye, Fei; Zhang, Dongming
Abstract : Three oligomeric phenylpropanoids [(+)/(–)-1 and 2 ] with new skeletons and a meroterpenoid (3 ) from Magnolia officinalis var. biloba were identified. Pharmacological studies showed(+)-1 and (–)-1 are PTP1B and α-glucosidase dual inhibitors. Abstract : Three unprecedented oligomeric phenylpropanoids with new carbon skeletons [(+)/(–)-maglignan A ((+)/(–)-1 ) and maglignan B (2 )] and an undescribed meroterpenoid [maglignan C (3 )] possessing an oxabicyclo [3.3.1] skeleton were obtained from the bark of Magnolia officinalis var. biloba. Compounds (+)-1 and (–)-1, a pair of enantiomeric trimers with novel oligomerization mode, which could be biosynthesized through oxidation, substitution, and hetero-Diels–Alder (HDA) reactions between C6–C3 units, exhibited significant inhibition of PTP1B and α-glucosidase with IC50 values from 0.448 to 2.16 μM. Molecular docking simulation was conducted to demonstrate the obtained results.